Evolutionary game and stability analysis of elderly care service quality supervision from the perspective of government governance - Wang, Qiangxiang; Liu, June; Zheng, Yue (Frontiers in Public Health, 2023)
To explore the optimal path for the government to govern the elderly care service market, a tripartite evolutionary game model, which is composed of local governments, private elderly care institutions and the public, is proposed in the paper. Furthermore, three mechanisms, i.e. dynamic penalty and static subsidy, static penalty and dynamic subsidy, dynamic penalty and dynamic subsidy, are designed. Under these different mechanisms, the stability of each subject's strategy choice is analyzed by using system dynamics simulation. The results show that: the introduction of dynamic mechanisms can compensate for the inability of static mechanisms to bring the system to a steady state. The dynamic penalty and dynamic subsidy mechanism allows the system to evolve to the desired point of stability. The self-discipline behavior of private elderly care institutions is positively correlated with penalties and reputation gains-losses, negatively correlated with subsidies, and not correlated with supervision rewards. Excessive subsidies will promote the collusion of private elderly institutions. This study would provide a reference for local governments seeking to develop effective regulatory policies for the elderly service market.